Diffusion‐weighted imaging of the high‐risk breast: Apparent diffusion coefficient values and their relationship to breast density. Issue 4 (13th September 2013) - O'Flynn, Elizabeth A.M.; Wilson, Robin M.; Allen, Steven D.; Locke, Imogen; Scurr, Erica; deSouza, Nandita M.
<x xml:space="preserve">Abstract</x> Purpose To document the apparent diffusion coefficient (ADC) of fibroglandular breast tissue in women at high‐risk of developing breast cancer and investigate the relationship between ADC and breast density. Materials and Methods Local research ethics approval was obtained. A total of 33 high‐risk women including 17 BRCA1/2 mutation carriers (mean age, 43 years) and 16 women postmantle irradiation (mean age 40 years) underwent diffusion‐weighted MRI between days 6 and 16 of their menstrual cycle. ADC histograms from a region of interest in fibroglandular tissue and mammographic breast density measurements were obtained. Mean, percentile ADC values (10th, 25th, 50th, 75th, 90th) and skew were compared for the two groups; ADC and mammographic breast density were correlated. Results Mean ADC values (×10−6 mm2/s) were 2017 ± 197 in postmantle irradiated women and 1827 ± 289 in BRCA1/2 mutation carriers (P = 0.035) with significant differences at all percentiles (P < 0.0001) but not skew (P = 0.44). ADC values showed weak positive correlation with mammographic breast density in BRCA1/2 mutation carriers (r = 0.51, P = 0.043) but not in postmantle radiotherapy patients (r = 0.49, P = 0.13). Conclusion Higher ADC values seen in fibroglandular tissue postmantle irradiation compared with BRCA1/2 mutation carriers has potential to improve tumor detection in these patients. Lack of correlation between ADC and breast density postmantle irradiation may be a result of microstructural changes. J. Magn. Reson. Imaging 2014;39:805–811. © 2013 Wiley Periodicals, Inc.